A New Attribution to Dunstaple. Issue 2 (14th August 2019) - Wright, Peter
Abstract: Since the publication of Bukofzer's edition of John Dunstaple's complete works in 1953, not one anonymous piece has been firmly attributed to the composer conjecturally. Scholars have understandably been reluctant to speculate on questions of authorship on the basis of style alone. At the same time it would be surprising if works by the most productive English composer of the period had not survived among the numerous anonymi that constitute such a high proportion of the fifteenth-century insular repertory. This article makes a case for Dunstaple's authorship of an anonymous Credo bearing the designation 'Anglicanum' in one of its sources. It argues this case on the basis of the work's close ties to some of the composer's early mass music, and to one of his Credo settings in particular, demonstrating striking links—structural, stylistic, textual, and transmissional—both with this Credo and another by Dunstaple.